Oi duck-billed platypus! - Kes Gray (London; Hodder Children's Books, 2020)
Oi! Where are duck-billed platypuses meant to sit? And Kookaburras and hippopotamuses and all the other animals with impossible to rhyme with names? Over to you Frog!
Keywords: Board books